The Application of Science and Technology in Law No. 28 of 2014 on Copyright for Lecturers at Universitas Muhammadiyah Papua - Herry M. Polontoh; Frans Reumi; Dudi Mulyadi; Tri Yanuaria; Ruth Kambuaya; Sobardo Hamonangan (Jurnal Insan Pengabdian Indonesia, 2025)
The title of this community service activity is "The Application of Science and Technology in Law No. 28 of 2014 on Copyright for Lecturers at Universitas Muhammadiyah Papua." This activity was conducted on August 1, 2024, and attended by 19 (nineteen) lecturers. The goal was to enhance the understanding and skills of lecturers in applying the Copyright Law, particularly related to academic works and research. The implementation methods included socialization, workshops, and mentoring. The socialization provided basic understanding of copyright and intellectual property protection. The workshop focused on practical training, such as how to register copyrights and understand the legal procedures. Mentoring, both in groups and individually, offered direct guidance to lecturers in applying the knowledge they had gained.The outcomes achieved included increased lecturer knowledge of copyright, an increase in the number of works registered, and the formation of a copyright oversight team within the university to ensure compliance with applicable regulations.